Person-centred care for dementia patients (back-end system development) - Lim, Josh (Nanyang Technological University, 2022)
Dementia is a broad term that describes a group of disorders which impair cognitive functions seriously enough to interfere with independent daily functioning. The preferred method of treatment for dementia is non-pharmacologic therapies, in particular Person-Centred Care, which is the tailoring of a patient’s healthcare delivery to their needs and preferences. Person-Centred Care (PEAR) is a software system that seeks to achieve this by streamlining person-centred care in the context of a dementia care centre. PEAR consists of both a web application and a smartphone application and has been in development since 2017. The main focus of this project was to improve the development workflow of future batches of developers. This was done through the improvement of the project management framework, as well as focusing on traceability, maintainability, and extensibility during development. The tangible outcomes of this project were the reworked notification subsystem and various project management tools that have been set up as part of the new project management framework